2018
DOI: 10.3390/molecules23020260
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Anti-Staphylococcal Potential of Honeys Produced in Northern Poland

Abstract: The antimicrobial activity of 144 samples of honeys including 95 products from apiaries located in Northern Poland was evaluated. The antibacterial activity of those natural products, their thermal stability, and activity in the presence of catalase was investigated by microdilution assays in titration plates. The MTT assay was performed for the determination of anti-biofilm activity. Spectrophotometric assays were used for the determination of antioxidant potential, total phenolic content, and ability to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 58 publications
(98 reference statements)
10
47
0
Order By: Relevance
“…This shows promise for the use of honey against multispecies biofilms, especially within wounds. However, the concentration of honey administered needs to be considered, as it has been demonstrated that sub-inhibitory concentrations of honey can improve biofilm formation in S. aureus, rather than inhibit it [16,95]. Therefore, more research is required to define the appropriate concentrations of honey to be administered for this purpose.…”
Section: Antibiofilm Propertiesmentioning
confidence: 99%
“…This shows promise for the use of honey against multispecies biofilms, especially within wounds. However, the concentration of honey administered needs to be considered, as it has been demonstrated that sub-inhibitory concentrations of honey can improve biofilm formation in S. aureus, rather than inhibit it [16,95]. Therefore, more research is required to define the appropriate concentrations of honey to be administered for this purpose.…”
Section: Antibiofilm Propertiesmentioning
confidence: 99%
“…This popular bee product is versatile and is effective against microbes [1][2][3][4], reducing inflammation [5], combating cancer [6], hypertension [7], and liver disease [8], aids in wound healing [3,9] and provides cough relief [10]. An important therapeutic quality of honey is its antimicrobial activity [11][12][13][14]. Investigations into alternative, natural antimicrobial agents such as honey is of immense importance to safeguard human and animal health.…”
Section: Introductionmentioning
confidence: 99%
“…It protects the bee against American Foulbrood and has potent antimicrobial activity [15,22]. Although honey may contain these compounds and enzymes, there is immense variability in the antimicrobial activities of honeys of different origins due to factors such as the species of bee [12,14], geographical location [23], soil type [24], floral source [25], season [26] and age of honey [11,27].…”
Section: Introductionmentioning
confidence: 99%
“…26 Although H 2 O 2 is an important factor in the bacterial growth inhibition, polyphenolic compounds and their interaction with H 2 O 2 are the key factors responsible for honey high antibacterial activity. 28 Other micro components honey glycoprotein fractions as antimicrobial peptide bee defensin-1 11,22 exhibited strong growth inhibition by binding and agglutination of bacterial cells or membrane permeabilization of bacterial cells. 29,30 Moreover, the presence of methylglyoxal(MGX) exhibited in manuka honey may modify some honey proteinaceous compounds and therefore affect the glucosidase activity 31 sharing in antimicrobial action.…”
Section: Antimicrobial Activity (In Vitro Assay)mentioning
confidence: 99%
“…There is an important correlation between high antioxidant and antimicrobial activity, 11 moreover, the antioxidant components present in honey [61][62][63] and EEP 61,64 play a great role in their immunomodulation properties. So, the above mentioned bioactive components at least have all antimicrobial, antioxidant and immunological boosting factors.…”
Section: Boosting Immunitymentioning
confidence: 99%